Safety, Security, and Disaster Preparedness Plan of AIMS as Perceived by Internal Stakeholders: Towards the Enhancement of Institutional Safety and Security Plan - Cabasal, Maria Celia C.; Lusiniara, Manolito T.; Alumia, Amador B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Employing descriptive-comparative design, the perception towards the safety, security and disaster preparedness of AIMS was taken from 167 employees and 343 students and strategically compared using T-test and analysis of variance (ANOVA). A standardized questionnaire adapted from the School Safety and Security Checklist by the New York State Police and the Virginia State Education Department was used as instrument during the data gathering period held last 1st Trimester of school year 2022-2023. Demographic profile and mean perception were also statistically treated using frequency, percentage and weighted mean. Based on the results, most of the employee respondents are newly-hired, single, not over 30 years old, physically fit and majority are females. They agreed that AIMS management have a safety and security management plan for its internal stakeholders. However, there are significant differences on their perception when grouped by Department, Position, and Years of Service at AIMS. Specifically, employees who are older and more mature seek improvement and enhancement on the services, facilities, and policies pertaining to safety. On the other hand, majority of the student respondents are male, BSMT first year students and claimed to be physically fit. Their perception towards the safety and security management of AIMS were higher compared to the employees. However, no significant difference was shown on their perception towards the safety and security management plan of AIMS when grouped according to their profile. For the school grounds, both respondents imply the need for parking facility improvement while on the school interior, it is recommended to conduct a psychological capability training and access to conflict resolution under the initiative of the Regiment Department.